Analisis Dan Perancangan Sistem Informasi Manajemen Aset “Sima” Dengan Menggunakan Qr (Quick Response) Code (Studi Kasus : RSUP Dr. Sitanala Tangerang) - Abdullah Muhajir; Eka Yuni Titik Artaningsih (CV. ITTC INDONESIA, 2025)
In the current era of the Industrial Revolution 4.0, all sectors implement automation carried out by machines or computerization. Whether it's the industrial sector, health services, information services, and even daily life can not be separated from what is called technology, the Central General Hospital Dr. Sitanala is one of the impacts of the industrial revolution 4.0 where the work process uses a computerized technology system. Hospital assets also require good management, because poor management can lead to a decrease in efficiency and also the quality of service at the hospital. Lack of employee awareness of assets/inventory items makes inventory items, not by initial placement data. With an application-based asset management information system through a QR Code (Quick Response) all Hospital assets are recorded and stored in a data storage (server). QR is a form of evaluation of barcodes that we usually see on a product, with QR all hospital asset data can be seen and traced for their existence so that the optimization of hospital assets goes well.